Biocompatible quaternized chitosan-based nanocomposite hydrogels with antibacterial and rapid hemostatic properties - Zhang, Juanni; Farhan, Mohd Said; Lv, Ruixue; Nur Fathin Shamirah, Daud; Jing, Zhanxin (Royal Society of Chemistry, 2025)
In this study, we developed a quaternized chitosan-based nanocomposite hydrogel by combining dual-network and nanocomposite technology. Firstly, quaternized chitosan (QCS) and chitin nanowhiskers (ChWs) were synthesized and characterized. The quaternized chitosan-based nanocomposite hydrogels were constructed by the radical polymerization of acrylic acid (AA) and acrylamide (AM) and the subsequent cooling process in the presence of QCS, ChWs, and Zn 2+ . The chemical structure and morphology of the synthesized hydrogels were analyzed using FT-IR and SEM, revealing that the nanocomposite hydrogels have a remarkable three-dimensional network structure. The effects of QCS, ChWs, and Zn 2+ content on the hydrogel's physical and biological properties were systematically investigated. The swelling behavior, mechanical strength, and antibacterial performance of quaternized chitosan-based nanocomposite hydrogels can be effectively modulated by varying their composition. An increase in QCS content led to a notable enhancement in mechanical properties. Specifically, the hydrogel containing 25% QCS exhibited a tensile strength of 391.9 kPa and an elongation at break of 495%. The increased QCS and Zn 2+ contents significantly improved the antibacterial properties of the nanocomposite hydrogels. The antibacterial rate against E. coli and S. aureus could reach up to 99%. Furthermore, the QCS-based nanocomposite hydrogels demonstrated good biocompatibility and rapid hemostatic ability. We expect that this simple strategy combining nanocomposite technology and dual-network technology will enrich the avenues for exploring hydrogels with excellent mechanical strength, antibacterial activity, and hemostatic performance for biomedical applications such as wound management, hemostatic materials, and infection control.